2013
DOI: 10.1073/pnas.1309143110
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in dopaminergic transmission precede neuron loss and dysfunction in a new Parkinson model

Abstract: The pathological end-state of Parkinson disease is well described from postmortem tissue, but there remains a pressing need to define early functional changes to susceptible neurons and circuits. In particular, mechanisms underlying the vulnerability of the dopamine neurons of the substantia nigra pars compacta (SNc) and the importance of protein aggregation in driving the disease process remain to be determined. To better understand the sequence of events occurring in familial and sporadic Parkinson disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
275
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(322 citation statements)
references
References 32 publications
23
275
0
Order By: Relevance
“…1H ). This result is consistent with a previous finding that ␣-syn mutations suppress transmitter release (Nemani et al, 2010;Lundblad et al, 2012;Janezic et al, 2013).…”
Section: To Generate Math5supporting
confidence: 93%
See 2 more Smart Citations
“…1H ). This result is consistent with a previous finding that ␣-syn mutations suppress transmitter release (Nemani et al, 2010;Lundblad et al, 2012;Janezic et al, 2013).…”
Section: To Generate Math5supporting
confidence: 93%
“…Consistently, we found that h-␣-syn A53T and h-␣-syn, but not h-␣-syn A30P , inhibited endocytosis. The lack of inhibitory effects of ␣-syn A30P might be due to its weaker membrane binding affinity than ␣-syn or ␣-syn A53T (Jo et al, 2002;Outeiro and Lindquist, 2003;Bussell and Eliezer, 2003). We could not exclude the possibility that the longer exposure of ␣-syn A30P in older mice inhibits endocytosis and exocytosis, considering that the ␣-syn A30P mutation is associated with late PD onset and incomplete penetrance (Krüger et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the mechanism of LRRK2 associated with these events that needs to be uncovered. For example, LRRK2 has been associated with Wnt signalling pathways 76, which are essential for the acute regulation of synaptic function; a function that is dysregulated in the premotor symptom stages of rodent models of PD 180. From this prospective, the involvement of LRRK2 in Wnt signalling is an exciting possibility that may give a reason for the alteration in gene expression, as well as disruption of vesicle trafficking 181, which are implicated in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in Parkinson's disease models with overexpression of wild-type a-synuclein show mainly an inhibitory effect of a-synuclein on neurotransmitter release [29][30][31][32][33][34], whereas two other studies come to the opposite conclusions [35,36]. In one of the latter increased synaptic activity was found in cultured hippocampal neurons acutely injected with a-synuclein.…”
Section: Function Of A-synuclein On Synaptic Activity and Transmittermentioning
confidence: 95%